WOMAN’S AMBITION IN MIRA NAIR’S VANITY FAIR - Laksmi Diana (JUPE : Jurnal Pendidikan Mandala, 2022)
This study aims to determine the existence of an ambitious side that is owned by the main female character, Rebecca Sharp (Becky) in the story in the film Vanity Fair. The results of the study show that the main female character, Rebecca Sharp, is ambitious, which has an impact on the content of the story in the film adaptation of the novel with the same title. This research is a library research using qualitative analysis.